Penerjemahan Alkitab Berbasis Church-Centric Bible Translation sebagai Model Pengabdian kepada Masyarakat pada Komunitas Suku Laut - Fredy Simanjuntak; Russ Perry; Matius Lim; Timotius Mangiring Tua Togatorop; Daniel Robert Tangkere (Institut Kristen Teologi Real Batam, 2026)
This community service program examines the process of Bible translation into the Seaman language, hereafter referred to as Seaman, using a church-centric Bible translation approach that places the local church and community as active participants in the translation process. The Seaman community is a coastal group facing serious challenges, including the endangerment of their mother tongue, low literacy levels, and the marginalization of cultural and religious identities. This program was implemented through collaboration between a theological institution, a Bible translation foundation, a local church, and Seaman families who still possess competence in the indigenous language. The method employed a participatory and contextual approach, involving intergenerational speakers as well as ongoing spiritual and community accompaniment. The results indicate that Bible translation functions not only as a means of Christian faith proclamation but also as a medium for language preservation, strengthening community identity, and empowering the local church in contextual mission. Furthermore, the process created spaces for interfaith dialogue within families and the wider community. This program demonstrates that Church-centric Bible translation can serve as a holistic, transformative, and relevant model of community service for indigenous and minority language communities. Keywords: bible translation, church-centric bible translation, community empowerment, community service, seaman community Abstrak Program pengabdian masyarakat ini mengkaji proses penerjemahan Alkitab ke dalam bahasa Seaman, selanjutnya disebut